Predation in the Ordovician and Silurian of Baltica. (2nd January 2017) - Vinn, Olev
Abstract: Signs of predation appear in the Middle Ordovician of Baltica. Shell repair dominates over the predatory borings in the Ordovician and Silurian. Predators attacked molluscs, brachiopods and tentaculitoids in the Ordovician and molluscs, tentaculitoids, brachiopods and ostracods in the Silurian. There is an increase in the number of prey species in the Late Ordovician, which could be related to the Great Ordovician Biodiversification Event. Molluscs are the favourite prey taxon in the Ordovician, but in the Silurian, molluscs became less dominant as the prey. This is probably not an artefact of preservation as Ordovician and Silurian molluscs are equally well preserved.